A Practical Model for Inbound Container Distribution Organization in Rail-Water Transhipping Terminal - Jiahao Zhao; Xiaoning Zhu; Yong Liu; Li Wang; Baicheng Yan (Journal of Control Science and Engineering)
Rail-water transportation is a crucial component of intermodal transportation system. Effective operation of rail-water intermodal transportation requires not only railway network and advanced handling equipment, but also scientific and reasonable transportation organization. In this paper, we first briefly introduced the coordination area and related concepts. Then an inbound container distribution organization model (ICDOM) was established taking into account many factors such as transhipping capacity, network capacity, and importance of containers, in order to minimize the total container-hours in the coordination area, which reflects the efficiency of inbound container distribution organization. Additionally, a genetic algorithm (GA) was developed and the optimization results were evaluated, which showed that both of the model and the algorithm were effective.